Comparable Postprandial Glucose Reductions with Viscous Fiber Blend Enriched Biscuits in Healthy Subjects and Patients with Diabetes Mellitus: Acute Randomized Controlled Clinical Trial - Jenkins, Alexandra L.; Jenkins, David J.A.; Wolever, Thomas M.S.; Rogovik, Alexander L.; Jovanovski, Elena; Božikov, Velimir; Rahelić, Dario; Vuksan, Vladimir (Croatian medical journal, 2008)
To compare the blood glucose-lowering effect of a highly viscous fiber blend (VFB) added to a starchy snack on postprandial glycemia between healthy participants and participants with diabetes mellitus. Ten healthy participants (4 men and 6 women, aged 28+/-2.6 years, body mass index [BMI], 24.3+/-0.8 kg/m(2)) and 9 participants with diabetes mellitus type 2 (3 men and 6 women, aged 68+/-3.8 years, BMI 28.8+/-1.2 kg/m(2)) on four separate occasions took either 50 g available carbohydrates as control biscuits, biscuits with 10 g of highly viscous fiber blend, white bread with 12 g of margarine, or white bread alone. Postprandial blood glucose response, glycemic index (GI), and palatability were determined. Mean (95% confidence interval) GI values of the viscous fiber blend biscuits were 26 (16-36) and 37 (27-47) GI units for healthy participants and participants with diabetes mellitus, respectively. These values were significantly lower than those of white bread, white bread with 12 g of margarine, and control biscuits (P<0.001, paired t test) both in healthy participants (GI 100, 108 [57-159], and 101 [44-158], respectively) and participants with diabetes mellitus (GI 100, 103 [79-127], and 94 [78-110], respectively). Viscous fiber blend significantly reduced the glycemic index by 74% (7.4 GI units/g of fiber) in healthy participants and by 63% (6.3 GI units/g of fiber) in participants with diabetes. The GI did not differ between control meals in both healthy participants and participants with diabetes. There were no significant differences in palatability among the types of meals, although participants with diabetes found the viscous fiber blend biscuits more palatable (P=0.002, t test). Viscous fiber blend is a very potent and palatable soluble fiber addition to a starchy snack, which is able to reduce the glycemic response to a similar extent in both healthy participants and individuals with diabetes mellitus. Biscuits with low GI, and possibly other viscous fiber blend fortified starchy foods, may potentially be a useful replacement of high GI snack foods in the diet.